Effect of river discharge fluctuation on water quality at three rivers in Endau catchment area, Kluang, Johor. - Aweng Eh Rak; Ismid Said; Maketab Mohamed (2010)
The water quality and river discharges was surveyed at three rivers in Endau cathment area (Sungai Dengar, Madek and Mengkibol) which was located in Kluang, Johor from November 2008 to August 2009 by using in-situ water quality measurement instruments and current meter. In-situ water quality measurement instruments were used to measure water quality and current meter was used to measure river water discharges. A total of five water quality parameters were measured namely pH, dissolved oxygen, conductivity, temperature and turbidity. Based on the results, it shows that there is a negative relationship between the values of all water quality variables measured (except turbidity) and discharge. Here we can suggest that, high water discharge will not influence the concentrations of pH, dissolved oxygen, conductivity and temperature except turbidity. Water becomes more turbid with the increased volume of water or with the increased of water discharge and clearer or less turbid during low water.